PENGARUH GOAL ORIENTATION, ACCOUNTABILITY PRESSURE TERHADAP AUDIT JUDGMENT PERFORMANCE DENGAN SELF EFFICACY DAN EFFORT SEBAGAI MEDIASI - Ratna Sari Dewi; Emrinaldi Nur; Alfiati Silfi (Program Studi Pendidikan Ekonomi Universitas Riau, 2019)
This study aims to analyze the factors that influence audit judgment performance.The population in this study is an independent auditor who works in the PublicAccounting Office in the entire Central Sumatra region. The sampling techniqueused purposive sampling method, namely the sample was chosen based on certainconsiderations in accordance with the objectives of the study. On the basis of thesampling technique, there were 60 samples to be examined, working at KAP inPekanbaru, Padang and Batam. Data analysis and hypothesis testing in this studywere conducted using the Structural Equation Model - Partial Least Square (SEMPLS)method. with WARP-PLS 6.0 as the software. The results showed that selfefficacy does not mediate the effect of goal orientation on audit judgmentperformance. While the Effort mediates Accountability pressure on audit judgmentperformance, this shows that the pressure of accountability drives the auditortowards effort, the higher the auditor's accountability pressure, the higher the effortthe auditor mobilizes in improving his performance.